Tesauros e ontologias: estudo de definições presentes na literatura das áreas das ciencias da computação e da informação, utilizando-se método analítico-sintético - Alexandra Moreira (2003)
This is a comparative analysis of the term ontology, used in the computer science domain, with the term thesaurus, used in the information science domain. The aim of the study is to establish the main convergence points between this two knowledge representation instruments and to point out their differences. In order to fulfill this goal a analytical-synthetic method was applied to extract the meaning underlining each one of the instruments selected definitions. The definitions were obtained from texts well accepted by the research community from both areas. The definitions were applied to a KWIC system in order to rotate the terms that latter were examined qualitatively and quantitatively. This research conclusion is that thesaurus and ontologies operate in the same knowledge level, the epistemological level, although with different origins and purposes.